Selektivitas Medium Cystine Tellurite Blood Agar (CTBA) terhadap Beberapa Isolat Bakteri - Sariadji, Kambang; Sunarno, Sunarno; Puspandari, Nelly; Muna, Fauzul; Rukminiati, Yuni (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2015)
Cystine tellurite blood agar (CTBA) medium is a selective medium for Corynebacterium diphtheriae culture. The presence of tellurite is a selectivity of this medium to inhibit the others bacteria. Others medium were used as a selective medium for the culture of Corynebacterium diphtheriae were tinsdale and Hoyle medium, but was recommended by the World Health Organization (WHO) were CTBA and hoyle medium. However, information about the selectivity of medium was recommended by WHO is still limited. The aims of study to determine the selectivity of medium against a number of others species bacteria on CTBA. A number of 24 isolates contains of different species Corynebacterium spp and others species were regrown, then all isolates were cultured in CTBA medium, incubated for 24 – 48 haours at 37°C. The growthing of colony in CTBA were observed. The results showed that 7 isolates for Corynebacterium species can grow well on medium CTBA, 5 isolates from different species showed growth in CTBA medium including Staphylococcus aureus, Streptococcus pneumoniae, Enterobacter sakazakii , Klebsiella pneumoniae and Candida albicans. Meanwhile the rest 12 isolates showed no growthing on CTBA medium. Therefore it can be concluded that the selectivity of the CTBA medium has limited capabilities